Peripheral Neuropathy and VIth Nerve Palsy Related to Randall Disease Successfully Treated by High-Dose Melphalan, Autologous Blood Stem Cell Transplantation, and VIth Nerve Decompression Surgery - C. Foguem; P. Manckoundia; P. Pfitzenmeyer; J.-L. Dupond (Case Reports in Medicine)
Randall disease is an unusual cause of extraocular motor nerve (VI) palsy. A 35-year-old woman was hospitalized for sicca syndrome. The physical examination showed general weakness, weight loss, diplopia related to a left VIth nerve palsy, hypertrophy of the submandibular salivary glands, and peripheral neuropathy. The biological screening revealed renal insufficiency, serum monoclonal kappa light chain immunoglobulin, urinary monoclonal kappa light chain immunoglobulin, albuminuria, and Bence-Jones proteinuria. Bone marrow biopsy revealed medullar plasma cell infiltration. Immunofixation associated with electron microscopy analysis of the salivary glands showed deposits of kappa light chains. Randall disease was diagnosed. The patient received high-dose melphalan followed by autostem cell transplantation which led to rapid remission. Indeed, at the 2-month followup assessment, the submandibular salivary gland hypertrophy and renal insufficiency had disappeared, and the peripheral neuropathy, proteinuria, and serum monoclonal light chain had decreased significantly. The persistent diplopia was treated with nerve decompression surgery of the left extraocular motor nerve. Cranial nerve complications of Randall disease deserve to be recognized.